Acute Fixation of Displaced Intra-articular Calcaneus Fractures Is Safe Using the Sinus Tarsi Approach. Issue 6 (June 2021) - Joseph, Noah M.; Benedick, Alex; McMellen, Christopher; Napora, Joshua; Wetzel, Robert; Sontich, John; Ochenjele, George
Abstract : Objective: To analyze the correlation between surgical timing and outcomes for calcaneus fractures treated using a sinus tarsi approach (STA). Setting: Single Level-1 trauma center. Design: Retrospective. Patients/Participants: Seventy consecutive intra-articular calcaneus fractures (OTA/AO 82C; Sanders II-IV) treated operatively using STA with a minimum of 1-year follow-up. Intervention: Open management using STA. Main Outcome Measurement: Surgery timing, wound complications, American Orthopaedic Foot and Ankle Society ankle and hindfoot and Patient-reported Outcomes Measurement System scores. Results: Patients were primarily men (68.6%) averaging 46 years (range, 18–77 years). Nineteen (27%) were obese, 27 (38.6%) were smokers, and 3 (4.3%) were diabetic, and 10 (14.3%) had open fractures. Sanders III fracture patterns were most common (45.7%). Mean time to surgery was 4.9 days (range, 0–23 days). Three patients (4.2%) developed postoperative infections requiring surgical debridement and antibiotics. Forty patients (57%) underwent operative repair within 72 hours of injury, 9 (22.5%) of which had open fractures. Of this group, only one patient developed wound necrosis. Restoration of Bohler angle and angle of Gissane and reductions in calcaneal varus angle and heel width were achieved (all P < 0.001). No differences in Ankle Society ankle and hindfoot or Patient-reported Outcomes Measurement System scores were noted between patients treated within or beyond 72 hours from injury. Conclusion: Intra-articular calcaneus fractures can be treated acutely within 72 hours of injury using STA with minimal wound complications and without compromising short-term functional outcome. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.